2011
DOI: 10.1029/2011ja016437
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle dependence of solar wind energy coupling to the thermosphere

Abstract: [1] Solutions to the differential equations describing the behavior of driven-dissipative systems are compared with measured exospheric temperatures (T ∞ ) and provisional Dst indices acquired during 38 magnetic storms between mid-2002 and 2008. The only storm selection criterion was the availability of solar wind and interplanetary magnetic field data to compute driving electric fields " VS . Globally averaged T ∞ was inferred from measurements by accelerometers on the GRACE satellites. Statistical regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A linear regression analysis shows that EthJ77*(J)=1.31·1017+1.216EthJ77(J). We tried higher‐order polynomial fits to the data presented in Figure 9 but were unable to find correlation coefficients >0.95. If there is reason to reanalyze the storms studied by Burke [2011] the given E th J77 budgets should be adjusted using .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear regression analysis shows that EthJ77*(J)=1.31·1017+1.216EthJ77(J). We tried higher‐order polynomial fits to the data presented in Figure 9 but were unable to find correlation coefficients >0.95. If there is reason to reanalyze the storms studied by Burke [2011] the given E th J77 budgets should be adjusted using .…”
Section: Discussionmentioning
confidence: 99%
“…On a global scale E th SW mimics the energy content of a driven‐dissipative system. The differential equation governing the behavior of such systems is dEitalicthSWdt=αEεitalicVSEthSWτE. The coupling α E and relaxation τ E coefficients were determined empirically to have a strong, solar cycle dependence [ Burke , 2011; Weimer et al , 2011]. E th SW traces representing numerical solutions of closely resembled those derived from orbit‐averaged GRACE measurements during the large magnetic storms of July and November 2004.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that the latter component could be used as a proxy for the response of the thermosphere to geomagnetic activity forcing. Several papers (Burke et al, 2009(Burke et al, , 2010Burke, 2011;Frey et al, 2014) have examined the density response to solar wind variations by treating the thermosphere empirically as a dissipative system, using exospheric temperature inferred from accelerometer measurements. Bhatnagar et al (2005) examined storm-induced variations in orbit-derived density near 200 km altitude during 2001.…”
Section: Time-dependent Response To the Solar Wind And Imfmentioning
confidence: 99%
“…They found that in the weaker events, the contributions of Joule heating and EPP are roughly equal, whereas in strong events, Joule heating dominates. Several papers (Burke et al, 2009(Burke et al, , 2010Burke, 2011;Frey et al, 2014) have studied the density response to solar wind variations by treating the thermosphere empirically as a dissipative system, using exospheric temperature inferred from accelerometer measurements. Weimer et al (2011) related Poynting flux derived from interplanetary magnetic field (IMF) measurements to exospheric temperature derived from CHAMP and GRACE, for possible use as a geomagnetic activity argument in empirical models.…”
Section: Geomagnetic Activity Responsementioning
confidence: 99%
“…It can not only get energy and momentum from the lower layer (i.e. the mesosphere) by the gravity wave and tide [1][2][3], but also from the solar wind through the magnetosphere [4]. Neutral particles are the main components in the thermosphere, where neutral wind is coupled with ion flow for a long time, especially in the polar region.…”
mentioning
confidence: 99%